Considerations for Active Labor Management with Oxytocin: More May Not be Better. Issue 4 (July 2020) - Simpson, Kathleen Rice
Abstract : Recent evidence suggests an oxytocin "rest" or discontinuing oxytocin once active labor has been established may be one way to minimize labor complications and decrease risk of cesarean birth for some women.